Effect of different type of soil in efficiency of thermal reduction in earth air heat exchanger (EAHE) - Nor Azimah , Mohd Nor'aini (2013)
Earth Air Heat Exchanger (EAHE) had shown to provide an effective and economical approach in reducing indoor building temperature as well as reducing electricity consumption and carbon dioxide emission. As an earth coupling, EAHE is designed to indirectly cool or heat buildings by ventilating outdoor air through a single or series of pipes buried underground. The efficiency of EAHE systems depend upon several factors, namely type of pipes, mineral compositions and the thermal conductivity of surrounding soils. Studies in the past have indicated that, different in temperature reduction were observed at different countries where the EAHE have been installed, primarily due to the effect of soil type. This study determines the efficiency of a simple, small scaled EAHE system by burying single pipe into different type of soil. Two soils were considered namely, original soil and crushed aggregate soil containing high quartz mineral content. The results indicated that a maximum temperature reduction of 7.5°C was achieved when the pipe was surrounded by crushed aggregate whereas; a much lower reduction of 3.8°C was observed for the natural soil. This study clearly shows that soil type plays a significant role in determining the efficiency of an EAHE system.